An Assessment of Entrepreneurship Intention Among Sunyani Polytechnic Marketing Students - Samuel, Yeboah Asuamah; Ernest, Kumi; Awuah, Jacob Baffour (International Review of Management and Marketing, 2013)
The aim of the paper is to assess the entrepreneurial intention among the students of Sunyani Polytechnic, and also to determine the motivators, and obstacles to entrepreneurial intentions. The study is based on quantitative exploratory survey design. The sample size for the study is 136 comprising of 94 males and 42 females, who were selected by convenient sample method. Primary data were obtained using self designed questionnaire which were administered by the researchers. Data were analysed using percentages, One-way ANOVA. Results indicated that there is high entrepreneurial intention among the respondents. It was also revealed that there are important motivators for intention as well as obstacles to setting up ones firm. The finding again indicated that demographic variables such as gender, age, religion affect responses given by respondents. It is recommended that, future research must be done in the public and private universities to provide support for these findings and also entrepreneurial education must be introduced into the tertiary institutions which are not currently offering entrepreneurship courses. Keywords: entrepreneurial intentions; entrepreneurship; motivation; obstacles, personality traits JEL Classifications: L26